2016
DOI: 10.24220/2318-0897v24n2a2959
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento da mucosite oral com laser de baixa potência: revisão sistemática de literatura

Abstract: Verificar qual o melhor protocolo de aplicação da laserterapia de baixa potência para prevenção e tratamento da mucosite oral químio e rádio induzida. Revisão sistemática de literatura sobre laserterapia na prevenção e tratamento da mucosite oral rádio e químio induzida. Foram utilizadas as indexações “mucositis”, “lowpower laser therapy”, na busca de estudos clínicos randomizados dos últimos 10 anos nas bases de dados de referência: PubMed, LILACS e Cochrane Library. A pesquisa resultou em 16 estudos clínicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
7
0
9
Order By: Relevance
“…Currently, laser therapy has been used in several areas of dentistry due to its technology that provides greater comfort to patients and reliability to the professional. 14,35,36 The studies by Albuquerque, Moraes and Sobral (2007) are in agreement with Cavalcante, Barros and Catão (2011) and Fiorentino et al (2015), reiterating the advantages of using LLLT, which according to these authors provides relief of acute and chronic pain, promoting immediate and temporary analgesia; It may also be incorporated in the treatment of oral mucositis, herpes, aphthous lesions, candidiasis, neuralgia, xerostomia, facial palsy, joint pain, inflammation and lesions in the oral mucosa, dentinal hypersensitivity, tem-poromandibular disorders, periodontal disorders, restorative, orthodontic and endodontic treatments, post-surgical moment and headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, laser therapy has been used in several areas of dentistry due to its technology that provides greater comfort to patients and reliability to the professional. 14,35,36 The studies by Albuquerque, Moraes and Sobral (2007) are in agreement with Cavalcante, Barros and Catão (2011) and Fiorentino et al (2015), reiterating the advantages of using LLLT, which according to these authors provides relief of acute and chronic pain, promoting immediate and temporary analgesia; It may also be incorporated in the treatment of oral mucositis, herpes, aphthous lesions, candidiasis, neuralgia, xerostomia, facial palsy, joint pain, inflammation and lesions in the oral mucosa, dentinal hypersensitivity, tem-poromandibular disorders, periodontal disorders, restorative, orthodontic and endodontic treatments, post-surgical moment and headache.…”
Section: Discussionmentioning
confidence: 99%
“…29 The use of the He-Ne low-level laser (632.8nm, 60mW, 2J/ cm2) applied daily before each radiotherapy session for seven weeks is a simple and non-traumatic technique for the prevention and treatment of mucositis of various origins, being able to reduce the severity and duration of oral mucositis associated with radiotherapy. 29,34,35 Studies performed by Bensadoun et al (1999) have shown a reduction in pain and an improvement in ingestion ability. The treatment is painless, little invasive (performed in the patient's oral cavity), low cost, and provides fast and safe application, with studies that prove its efficacy in the pro-phylaxis and treatment of oral mucositis as well as of various other organic disorders.…”
Section: Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…A mucosite oral é outra manifestação bucal que se inicia aproximadamente 15 dias após o começo da radioterapia; consiste em um dano à mucosa oral e ao trato gastrointestinal, apresentando-se em graus variados de eritema e podendo evoluir para ulcerações. Uma das alternativas terapêuticas para a mucosite oral é a laserterapia de baixa potência, um tratamento não invasivo que promove rápida cicatrização e analgesia 12,13 .…”
Section: Introductionunclassified
“…Despite the various therapeutic possibilities available, the best protocol to be used should consider the specific needs of each patient and the cost-benefit ratio [8][9][10] . So, from this reality, this unpublished study proposed to create and test the Copaíba-based Oral Hydrogel, after approval of the project by the Research Ethics Committee (Approval Protocol: 2.143.119) whose partial result is exemplified below in this case report.…”
mentioning
confidence: 99%